Effects of maternal and post-weaning supplementation with microbe-derived antioxidants on sow and piglet performance, oxidative status, and gut microbiota - Tang, Jiayong; Wang, Yifan; Zhou, Qiang; Fang, Zhengfeng; Lin, Yan; Xu, Shengyu; Feng, Bin; Zhuo, Yong; Jiang, Xuemei; Zhao, Hua; Wu, De; Che, Lianqiang (Frontiers in Veterinary Science, 2025)
The antioxidants were found to improve inflammatory responses and redox status. This study investigated the effects of maternal and post-weaning supplementation with microbe-derived antioxidants (MA) on sow performance, redox status, and fecal microorganisms, as well as the growth performance, inflammatory responses and intestinal microbiota of weaned piglets. Sixty multiparous sows were randomly allocated to the control group (CON, basal diet) and the MA group (basal diet supplemented with 2.0 g MA/kg) from d 90 of gestation to d 24 of lactation, according to the parity and body condition. At weaning, a total of 80 piglets per group were selected and randomly assigned to either the basal diet or the MA-supplemented diet, with 10 pens per group and 4 piglets per pen, for a period of 21-day trial. Results showed that maternal MA supplementation increased litter size at weaning (p < 0.05) and the milk contents of dry matter (p = 0.08) and fat (p = 0.09), while decreasing the plasma activities of alanine aminotransferase and aspartate aminotransferase in sows on d 24 of lactation (p < 0.05). Moreover, maternal MA supplementation reduced plasma malondialdehyde concentration (p ≤ 0.01) in sows at farrowing and weaning, as well as catalase activity at weaning (p = 0.01), and tended to increase total antioxidant capacity at farrowing (p = 0.08). Additionally, the fecal contents of butyrate (p = 0.04) and propionate (p = 0.09) were higher in sows receiving the MA diet at d 24 of lactation. In post-weaning piglets, maternal MA supplementation increased average daily gain (p = 0.07) and average daily feed intake (p < 0.05) throughout the period, and increased plasma immunoglobulin G and interleukin-10 concentrations (p < 0.05). Additionally, either maternal or post-weaning MA supplementation positively influenced the gut microbiome of both sows and weaned piglets. In conclusion, maternal MA supplementation during late gestation and lactation increased litter size at weaning, which may be associated with the improved milk quality and redox status. Furthermore, maternal MA supplementation may enhance the growth performance of post-weaning piglets, potentially linking to the improvements in immunological parameters and gut microbiome.